PORTARIA PRR4 Nº 9, DE 25 DE JANEIRO DE 2005 - Maria Hilda Marsiaj Pinto (BSMPF, Brasília, DF, p. 13, 2. quinzena jan. 2005., 2005)
Designa servidores para as funções de Coordenador de Secretaria de Núcleo.